Analisis Terhadap Ketua Yayasan yang Rangkap Jabatan Di Indonesia: Sebuah Potensi Konflik Kepentingan - Xavier Nugraha (DOKTRINA: JOURNAL OF LAW, 2020)
The aim of this legal research is toto analyze the relationship between the head of the foundation who has concurrent positions so that there is the potential to create a conflict of interest. The formulation of the problem in this study is First, namely, how is the chairman of the foundation's arrangement in Indonesia? and Second, namely, how are provisions related to concurrent positions that can cause conflicts of interest to the chair of the foundation in Indonesia? This research is legal research using a statutory and conceptual approach. Based on this research, it was found that there are two models of concurrent positions that have the potential to cause conflicts of interest, namely concurrent positions with internal positions and concurrent positions with external positions. In Indonesia, related to the chairman of the foundation, what is banned is a dual position with an internal position, such as supervisors and supervisors. Associated with the chairman of a foundation who has concurrent positions with an external position, such as being an administrator in a different foundation is not prohibited, but if the concurrent positions cause the foundation's chairman, it harms the foundation, then the chairman of the foundation can be dismissed, and even has the potential to be held personally responsible.